Synthesis of D-π-A type 4,5-diazafluorene ligands and Ru (II) complexes and theoretical approaches for dye-sensitive solar cell applications - Erden, Ibrahim; Hatipoglu, Arzu; Cebeci, Caner; Aydogdu, Seyda (ELSEVIER, 2020)
In this paper, we synthesized and characterized 4,5-diazafluorene-derived ligands and their Ruthenium complexes containing conjugate and anchor groups. These groups on the designed molecules were investigated for the contribution of electrical transformation efficiency in prepared dye sensitive solar cell (DSSC). The structure of the compounds was determined by FTIR, UV-Vis Spectrometer, NMR, and MS spectroscopic data. Theoretical calculations were performed with density functional theory (DFT) methods. The electronic, spectral and quantum chemical properties of the ligand and complex molecules were calculated by using B3LYP/6-311++G(d,p)/SDD basis set. In order to determine the electron density on the molecules, we compared the results of the theoretical studies with the measured photovoltaic properties of DSSC devices. The photovoltaic cell efficiencies (PCE) of the devices were in the range of 0.22-1.05% under simulated AM 1.5 solar irradiation of 100 mW cm(-2), and the highest open-circuit voltage (V-oc) reached 0.628 V. The C4 compound DSSC provided 1.05% efficiency, while the DSSC Ru -C4 complex exhibited performance at 0.35% efficiency under illumination. According to this result, it was observed that the electron movement on the Ru(II) complexes could not reach the anchor group as much as the ligands. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: 4,5-Diazafluorene; Schiff base; Dye-sensitized solar cell; DFT; ORGANIC-DYES; ACCEPTOR; PERFORMANCE; DERIVATIVES; CONVERSION; DSSCS; Chemistry